Validity of screening tools for activity limitation and cognitive dysfunction in patients with HIV associated neurocognitive disorders - Smith, Elizabeth Barbara (My University, 2020)
Introduction: Human Immunodeficiency Virus Neurocognitive Disorders (HIV NCD) are prevalent in South Africa. Human immunodeficiency virus associated neurocognitive disorder results in impairments in cognition and instrumental activities of daily living which can reduce quality of life. To effectively use limited health care resources, efficient and appropriate screening tools are needed to identify those who need a more comprehensive assessment and to guide care. Methods: This study used a descriptive design to determine the efficacy and limitations of three screening tools used in tertiary clinics in Gauteng. The study occurred in two phases, each using a different methodology. In phase one, the quantitative strand, patient-participants were screened using the International HIV Dementia Scale (IHDS), Montreal Cognitive Assessment (MoCA) and World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0). The results were used to identify if those scoring 11 or below on the International HIV Dementia Scale, presented with cognitive dysfunction and activity limitations. These results were analysed using Spearman’s correlation coefficient for correlation of the International HIV Dementia Scale, to the Montreal Cognitive Assessment and World Health Organization Disability Assessment Schedule 2.0, and their convergence analysed. In phase two, the qualitative strand, the perceptions and experiences of health professionals in the field, on the efficiency and efficacy of these three tools, were explored in group interviews. Results: All 55 patient-participants, scoring 11 and below on the International HIV Dementia Scale, were found to have cognitive dysfunction and activity limitations, on the Montreal Cognitive Assessment and World Health Organization Disability Assessment Schedule 2.0,respectively. The cultural appropriateness of the Montreal Cognitive Assessment, and impact of mood and cognition on the World Health Organization Disability Assessment Schedule 2.0, for the cohort, was questioned in both phases of the study. The International HIV Dementia Scale total score was found to have clinically irrelevant correlations to the Montreal Cognitive Assessment and World Health Organization Disability Assessment Schedule 2.0 total scores, in the cohort. Therefore, these tools could not be used interchangeably in the screening of human immunodeficiency virus associated neurocognitive disorders. Conclusion: The screening tool administration should be standardised, and the results used with caution due to the limitations identified. Those with professional clinical reasoning should preferably use these tools. Further research is required to develop population appropriate screening tools, which will improve the efficiency and effectiveness of guiding care in human immunodeficency virus associated neurocognitive disorders
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy, 2020